2014
DOI: 10.1007/s11164-014-1725-3
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase inhibitory activity of supernatant and semi-purified extracts from squid pen fermented with Burkholderia cepacia TKU025

Abstract: Reports of tyrosinase inhibitors from microorganisms are rare. The tyrosinase inhibitory activity was found from the culture supernatant of Burkholderia cepacia TKU025 with 1 % squid pen as the sole carbon/nitrogen source. The fourth-day supernatant showed the strongest tyrosinase inhibitory activity (500 U/ml) and the highest total phenolic content (789 lg/ml GAE). The supernatant was further purified by liquid-liquid partition, and it was found that the methanol extract exhibited the lowest IC 50 value of 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Chitin, chitosan, colloidal chitin, and water soluble chitosan have commonly been used as the major carbon/nitrogen (C/N) sources for the isolation of strains producing chitinolytic enzymes and the production of chitinolytic enzymes by these isolated strains [ 9 , 15 , 16 , 17 , 18 ]. To cut down fermentation expenses, the inexpensive materials of shrimp heads, shrimp shells, crab shells, and squid pens have recently been evaluated as the sole C/N sources for the production of bioactive compounds [ 5 , 6 , 9 , 12 , 13 , 14 , 15 , 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ,…”
Section: Introductionmentioning
confidence: 99%
“…Chitin, chitosan, colloidal chitin, and water soluble chitosan have commonly been used as the major carbon/nitrogen (C/N) sources for the isolation of strains producing chitinolytic enzymes and the production of chitinolytic enzymes by these isolated strains [ 9 , 15 , 16 , 17 , 18 ]. To cut down fermentation expenses, the inexpensive materials of shrimp heads, shrimp shells, crab shells, and squid pens have recently been evaluated as the sole C/N sources for the production of bioactive compounds [ 5 , 6 , 9 , 12 , 13 , 14 , 15 , 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ,…”
Section: Introductionmentioning
confidence: 99%
“…This result indicated that the culture conditions for the production of S. speibonae TKU048 exochitinase by using only chitinous fishery byproducts to provide the source of C/N were successfully optimized. Until now, conversion of abundant and low-cost chitinous materials by microbial activity to produce bioactive compounds has received great attention [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31]. Consequently, the current results could be promising in providing a novel beneficial application of shrimp heads—a chitin-containing byproduct from fishery processing—in producing exochitinase via S. speibonae TKU048.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, these chemical procedures encounter several drawbacks when these chemical procedures are applied, such as the release of alkaline wastewater containing a high concentration of protein [11]. In green applications , those chitin-containing byproducts could also be used as the nutrition sources for microorganism bioconversion to produce numerous bioactive compounds, for instance, proteases [9,11,12], chitinases/chitosanases [2,4,13,14,15,16,17,18], α-glucosidase inhibitors [19,20,21,22,23,24,25], exopolysaccharide [26,27,28], tyrosinase inhibitors [29,30], or chitin [1,31,32,33].…”
Section: Introductionmentioning
confidence: 99%